Simultaneous Quantification of Syringic Acid and Kaempferol in Methanolic Extract of Cleome viscosa Linn. by Using Validated HPTLC-Densitometric Method - Shankar, Urvija; Nirala, Vijay Kumar; Shukla, Pushpendra Kumar; Srivastava, Sharad (Indian Journal of Pharmaceutical Education and Research, 2022)
Cleome viscosa Linn. (Capparaceae) commonly known as “Hurhur”, is a traditional medicinal plant used in the treatment of various ailments such as fever, inflammation, liver disorder, ulcer stomachache etc. In the present study, pharmacognostical and pharmacological evaluation of Cleome viscosa were done, on the basis of traditional claim. A validated HPTLC method was also developed for the simultaneous quantification of bioactive compounds i.e. syringic acid and kaempferol in C. viscosa. The chromatogram of syringic acid and kaempferol were developed by using tertiary mobile phase toluene: ethyl acetate: formic acid (7: 3: 0.5) and scanned at 278 nm and 370 nm. The developed method was found to be specific, linear, precise and accurate as per the standard protocol of ICH guidelines. In-vitro antioxidant, anti-inflammatory and anti-diabetic potential of the species were evaluated and found that C. viscosa have satisfactory potential, may be due to identified marker compounds. This study will be helpful in future for standardization, quality control and confirmation of the right plant material and monitoring of batch to batch consistency of finished herbal products using C. viscosa as an ingredient.
Keywords: Cleome viscosa; HPTLC; Syringic acid; Kaempferol; in-vitro